THE INFLUENCE OF INFORMATION TECHNOLOGY ON JOB SATISFACTION AND ORGANIZATIONAL COMMITMENT - Terek Edit; Vukonjanski Jelena; Cvetkoska Violeta; Mitić Siniša; Nikolić Milan (Dynamic Relationships Management Journal (DRMJ), 2018)
This paper presents the results of a study of the impact of information technology (IT) on job satisfaction (JS) and or ganizational commitment (OCM) in companies in Serbia. To measure the state of information technology in companies in Serbia, six items were defined: the possession of modern IT, using (i.e., the application of) modern IT, use of modern IT, the training of employees to work with modern IT, the motivation of employees to work with modern IT, and the importance that management places on modern IT. The research relates to the study of the impact of such defined in formation technology items on job satisfaction and organizational commitment. The data were obtained from a ques tionnaire completed by N = 380 middle managers from 102 companies in Serbia. The main conclusions of the research are as follows. The average values for the items of information technology are slightly above the average, indicating the good state of information technology in companies in Serbia. The perspective is also good, because the highest average value is for the importance that management places on modern IT. All correlations between information tech nology items and the observed organizational performance (job satisfaction dimensions and organizational commit ment dimensions) are statistically significant, strong, and positive. The most important correlations of information technology are with the following items: the motivation of employees to work with modern IT, the importance that management places on modern IT, and use of modern IT. From the observed organizational performance, the strongest correlations are with communication, nature of work, and organizational identification. Furthermore, regression anal ysis shows a predictive effect of information technology items on the observed organizational performance. Of all in dependent variables, the impact of the motivation of employees to work with modern IT is especially evident, as is the role of the importance that management places on modern IT. The recommendations to top managers are to con tinuously and systematically invest in the purchase and maintenance of modern information technology, and to mo tivate employees to work with modern information technology. The effects of these investments and efforts will be reflected through better business results, and the improvement of the level of numerous organizational performance indicators, such as job satisfaction and organizational commitment of employees.